2023
DOI: 10.1177/17474930231164024
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in stroke outcomes in Aotearoa New Zealand: A national linkage study

Abstract: Background: Ethnic differences in post-stroke outcomes have been largely attributed to biological and socioeconomic characteristics resulting in differential risk factor profiles and stroke sub-types, but evidence is mixed. Aims: This study assessed ethnic differences in stroke outcome and service access in New Zealand (NZ) and explored underlying causes in addition to traditional risk factors. Methods: This national cohort study used routinely collected health and social data to compare post-stroke outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…76 (1.07-1.89)]. The substudy, using health administrative data, increased the study power and controlled for socioeconomic factors (Denison et al, 2023). Among 762 Māori and 6,117 non-Māori stroke patients Māori were more likely to have an increased odds of death at 3,6, and 12 months with ORs 1.5-1.7 (1.2-2.1) and these findings persisted after controlling for socioeconomic deprivation.…”
Section: Stroke Outcomes In Ma ¯Orimentioning
confidence: 99%
“…76 (1.07-1.89)]. The substudy, using health administrative data, increased the study power and controlled for socioeconomic factors (Denison et al, 2023). Among 762 Māori and 6,117 non-Māori stroke patients Māori were more likely to have an increased odds of death at 3,6, and 12 months with ORs 1.5-1.7 (1.2-2.1) and these findings persisted after controlling for socioeconomic deprivation.…”
Section: Stroke Outcomes In Ma ¯Orimentioning
confidence: 99%
“…While there do appear to be some geographical differences, for example, increased intracranial stenosis in Far Eastern populations, 7 differences in access to services are likely to be more important in determining stroke outcome. This is highlighted in a study by Denison et al 8 from New Zealand in which they showed worse stroke outcomes in Maori, compared with European, New Zealanders. Importantly, they report that disparities in care and outcomes following stroke were independent of traditional risk factors, suggesting they may be attributable to differences in stroke service delivery rather than patient factors.…”
mentioning
confidence: 94%
“…This configuration excludes or inadequately addresses the diverse health needs of minority populations, including fat communities. In Aotearoa NZ, the healthcare system reflects the colonial roots from which it was developed (Denison et al, 2023;Moewaka Barnes & McCreanor, 2019). The health system that was introduced by colonisers to mirror their own system in Britain, completely disregarded any indigenous knowledge, practices and beliefs, rather prioritising patriarchal and colonial values Graham & Masters-Awatere, 2020;Moewaka Barnes & McCreanor, 2019;Warbrick et al, 2019).…”
Section: Fatphobia and Discrimination In Healthcarementioning
confidence: 99%